Informe práctica profesional en la Secretaria de Planeación e Infraestructura del Municipio de Chipaque Cundinamarca (2021)
The Municipal Mayor's Office of Chipaque Cundinamarca, in the Planning and Infrastructure office, multiple functions of a civil engineer are derived, several activities have been proposed that are notified daily and are carried out in the office, with an intensity of 9 hours a day, the following are carried out activities such as planning support; Construction licenses, risk management visits, architectural plans, reports of solutions to housing impacts, budget calculations, market studies for projects, among others.